Genomic Profiling Reveals the Molecular Landscape of Gastrointestinal Tract Cancers in Chinese Patients - Zhu, Chunrong; Zhu, Liangjun; Gu, Yanhong; Liu, Ping; Tong, Xiaoling; Wu, Guozhong; Zhu, Wenyu; Shen, Wenxiang; Bao, Hua; Ma, Xiangyuan; Yu, Ruoying; Wu, Xue; et al. (Frontiers in Genetics, 2021)
Gastrointestinal tract cancers have high incidence and mortality in China, but their molecular characteristics have not been fully investigated. We sequenced 432 tumor samples from the colorectum, stomach, pancreas, gallbladder and biliary tract to investigate cancer-related mutations and detail the landscape of microsatellite instability (MSI), tumor mutation burden (TMB), and chromosomal instability (CIN). We observed the highest TMB in colorectal and gastric cancers, and the lowest TMB in gastrointestinal stromal tumors (GIST). Twenty-four hyper-mutated tumors were identified only in colorectal and gastric cancers, with a significant enrichment of mutations in the polymerase genes (POLE, POLD1, and POLH), and mismatch repair (MMR) genes. Additionally, CIN preferentially occurred in colorectal and gastric cancers, while pancreatic, gallbladder, and biliary duct cancers had a much lower CIN. High CIN was correlated with a higher prevalence of malfunctions in chromosome segregation and cell cycle genes, including the copy number loss of WRN, NAT1, NF2 and BUB1B, and the copy number gain of MYC, ERBB2, EGFR and CDK6. In addition, TP53 mutations were more abundant in high-CIN tumors, while PIK3CA mutations were more frequent in low-CIN tumors. In colorectal and gastric cancers, tumors with MSI demonstrated much fewer copy number changes than microsatellite stable (MSS) tumors. In colorectal and gastric cancers, the molecular characteristics of tumors revealed the mutational diversity between the different anatomical origins of tumors. This study provides novel insights into the molecular landscape of Chinese gastrointestinal cancers and the genetic differences between tumor locations, which could be useful for future clinical patient stratification and targeted interventions.